2021
DOI: 10.1002/alr.22886
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic sinus surgery for chronic rhinosinusitis: 22‐item Sino‐Nasal Outcome Test 5‐year results

Abstract: Background Currently, limited data exist as to long‐term disease‐specific outcomes after endoscopic sinus surgery (ESS) for chronic rhinosinusitis (CRS). In this report, we present outcomes data collected over 5 years in a large prospective cohort of patients who underwent surgical treatment for CRS. Methods Patients who completed the 22‐item Sino‐Nasal Outcome Test (SNOT‐22) before ESS were asked to complete the same survey at yearly intervals for 5 years thereafter. The impact of patients’ demographics and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…26 Sinus-specific opacification has also been shown to not be correlated with CRS symptomatology. 27 Although the evidence has been conflicting, 28,29 some studies have shown that greater radiographic CRS disease severity may be associated with better outcomes after ESS [30][31][32] and one retrospective study has suggested that symptoms/ revision ESS rate may not be improved by ESS beyond affected sinuses. 33 In comparison, other studies have shown patients with minimal radiographic evidence of sinus disease but who have medically recalcitrant symptoms of suspected sinonasal origin can experience significant improvement in QOL from ESS.…”
Section: Discussionmentioning
confidence: 99%
“…26 Sinus-specific opacification has also been shown to not be correlated with CRS symptomatology. 27 Although the evidence has been conflicting, 28,29 some studies have shown that greater radiographic CRS disease severity may be associated with better outcomes after ESS [30][31][32] and one retrospective study has suggested that symptoms/ revision ESS rate may not be improved by ESS beyond affected sinuses. 33 In comparison, other studies have shown patients with minimal radiographic evidence of sinus disease but who have medically recalcitrant symptoms of suspected sinonasal origin can experience significant improvement in QOL from ESS.…”
Section: Discussionmentioning
confidence: 99%
“…15 Endoscopic sinus surgery (ESS) is a well-established treatment option for CRS that has broadly been shown to produce durable, long-term improvements in quality of life. [16][17][18][19] Within-subject comparisons have demonstrated that the large majority of females and males experience significant quality of life improvements after ESS, 7,9,20 although up to 20% of patients may require additional surgery within 5 years of the primary operation. 21,22 Moreover, female gender has repeatedly been identified as a risk factor for ESS revision.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic rhinosinusitis (CRS) is a condition that affects millions of people worldwide and has a detrimental impact on quality of life similar to diseases such as heart failure and chronic obstructive pulmonary diseases 1,2 . Endoscopic sinus surgery (ESS) has revolutionized CRS management and offers high rates of quality of life improvement and symptom severity reduction in patients who do not respond to medical therapy 3–5 . However, the decision to undergo ESS is complex and multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…medical therapy. [3][4][5] However, the decision to undergo ESS is complex and multifactorial. Despite meeting candidacy for surgery, patients may delay undergoing ESS for a variety of reasons.…”
mentioning
confidence: 99%